Forgotten Transports to Belarus - Pribyl, Lukas (Czech Republic, 2008)
It is the second of the four 90-minute-long films by Lukáš Přibyl, which are a mosaic of memories of the Jews from Bohemia and Moravia who were deported into the concentration camps and ghettoes in Latvia, Belarus, Estonia and eastern Poland. Those were places, which, unlike the infamous Auschwitz, Treblinka, Dachau or Terezín, are not widely discussed, but which witnessed equally cruel destinies of hundreds of thousands of people.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films